Potential role of lewis acid-base adducts in enhancing stereoselectivity in ziegler-natta catalysts: a DFT study - Raj, K. Vipin; Gupta, Virendra Kumar; Vanka, Kumar (Journal of Physical Chemistry C, 2023)
Ziegler-Natta (Z-N) systems have been well established as heterogeneous catalysts that produce isotactic polypropylene and polyethylene with great efficiency. Such systems benefit considerably from donors (Lewis bases), whose addition significantly improves the stereoselectivity of polymerization. There is a consensus that the primary role of the external donors is to coordinate at the vacant site created by the extraction of internal donors and thus maintain the stereoselectivity. However, the bite difference between internal donors such as phthalates or succinate derivatives and external donors such as alkoxysilanes raises the question of how external donors can effectively replace internal donors. In order to investigate this, we have chosen four external alkoxysilane donors: (1) diisopropyl dimethoxysilane, (2) dicyclopentyl dimethoxysilane, (3) disec-butyl dimethoxysilane, and (4) sec-butyl(methyl) dimethoxysilane. DFT studies reveal that the bite difference problem can be overcome by the favorable formation of adducts between the alkoxysilane external donors and AlEt2Cl in the Z-N systems. These adducts tend to coordinate in the vicinity of the active site. Furthermore, our findings demonstrate the potential of these Lewis acid-base adducts to enhance the stereoselectivity of Z-N catalysts significantly.